Síntese e avaliação biológica de Arilidrazoimidazóis, Arilidrazopirimidínicos e Quinolin-4-Hidrazotiazolidinas sobre Amastigotas de Leishmania chagasi e potencial antitumoral - Santos Júnior , Paulo Fernando da Silva (2017)
Leishmaniasis refers to the second largest cause of protozoan-related lethal infectious diseases, affecting about 12 million people in 98 countries, with 96% coming from the visceral (Leishmania chagasi). With regard to the treatment of these diseases, the therapeutic arsenal against leishmaniasis is limited and ineffective with drugs used for more than 70 years. Similarly, cancer is among the leading causes of death in the world. Of the 58 million deaths in 2005, 7.6 million (13%) were caused by cancer. Over 70% of these deaths occur in underdeveloped and developing countries, where resources available for cancer prevention, diagnosis and treatment are limited or non-existent. The aim of this study was to synthesize and evaluate the biological activities against tumoral strains, as well as amastigotes of the L. chagasi parasite of new arylimidazole / pyrimidine derivatives and quinolin-4-hydrazino thiazolidine via molecular hybridization / rigidification, characterized by ¹³, ¹³C NMR spectroscopy , IV and HPLC-UV, all of which are unpublished in the literature. Thus, 8 imidazole / pyrimidine end compounds as well as 7 quinolin-4-hydrazino thiazolidine end compounds were obtained. Comparatively, the synthetic methodology via microwave irradiation was satisfactory for imidazole / pyrimidine compounds (85-95%, 20-40min) and 65-80% for 24h. For the quinolin-4-hydrazino thiazolidine series, yield was obtained between 87-95% (20-55min) via sonication, comparing to 43-80%, for 24-36h, with purity between 90-98%. Substances (72), (75) and (76) showed a high cytotoxic activity against one of the human cancer cell lines used, where substances (72) and (75) tested. However, the substance (72) showed a relevant cytotoxic potential against the HL-60 tumor line, presenting IC50 = 2.4 μM, being therefore the most potent in this lineage.